In Silico Screening and Designing Synthesis of Cinchona Alkaloids Derivatives as Potential Anticancer - Hanafi, Muhammad; Rosmalena, Rosmalena; Prasasty, Vivitri Dewi; Udin, Linar Zalinar; Primahana, Gian (Journal of Tropical Life Science, 2017)
P-glycoprotein (P-gp) resistance in cancer cells decreases intracellular accumulation of various anticancer drugs. This multidrug resistance (MDR) protein can be modulated by a number of non-cytotoxic drugs. We have screened 30 chincona alkaloids derivatives as a potent P-gp inhibitor agent in silico. Hereby, we report the highest potential inhibitions of P-gp is Cinchonidine isobutanoate through molecular docking approach. with affinity energy -8.6 kcal/mol and inhibition constant, Ki is 4.89 x 10-7 M. Cinchonidine isobutanoate is also known has molecular weight below 500, Log P value 3.5, which is indicated violation free of Lipinski`s rule of five. Thus, Cinchonidine isobutanoate is the most potent compound as anticancer compare to other Cinchona alkaloids. Ultimately, we design Cinchonidine isobutanoate for further lead synthesis by using DBSA, act as a combined BrÃ¸nsted acid-surfactant-catalyst (BASC) to obtain high concentration of organic product by forming micellar aggregates which is very powerful catalytic application in water environment.